Analisis Dampak Transportasi Online terhadap Kesejahteraan Sosial pada Komunitas Gojek di Cempaka Putih Jakarta Pusat - Sobri Abben Sarbeni; Widiyono Widiyono; Imam Susanto (JAMBIS : Jurnal Administrasi Bisnis, 2021)
Impact is a collision, an effect that results from both positive and negative. Impact simply can be interpreted as influence or effect. Impacts can also be a follow-up process of implementing internal controls. In this study, we will explain the impact of online motorcycle taxis, especially GOJEK on social welfare in the Cempaka Putih Gojek Community. GOJEK is a social-minded technology company that aims to improve the welfare of its partners in various informal sectors in Indonesia. This study aims to find out how the impact of online motorcycle taxis on social welfare in the Gojek Community in Cempaka Putih, Central Jakarta. This study uses the theory of the social change impact and social welfare as well as field research with a qualitative method approach. The subjects of this study are GOJEK drivers in the GOJEK Community in Cempaka Putih. The formulation of the problem studied was how the impact of online motorcycle taxis on social welfare in the GOJEK community in Cempaka Putih, Central Jakarta. Collecting data through observation, interviews (interviews) and documentation. As for the data analysis using descriptive qualitative, the data that has been obtained is then compiled and classified so that it can answer from the formulation of the problem above. The results of this study indicate that: the impact of online motorcycle taxi on social welfare in the GOJEK Cempaka Putih community, which is a GOJEK driver is more useful because the income received by drivers is greater than income in previous jobs or unemployed. This is the reason for the mobility of workers and has an impact on increasing the social welfare of GOJEK drivers in the Gojek Cempaka Putih Community.